Management information systems : - Post, Gerald V. (McGraw-Hill / Irwin, 2003)
Management Information Systems focuses on how managers can apply IT tools to solve management problems, organize businesses and systems, and find new opportunities. It remains unique in its emphasis on databases as crucial to any business application. A detailed sample database is included with each copy of the book